Implementation of i Reading and Literacy Tourism Program at Banjar City Public Library - Rahmat Sudarmaji; Machsun Rifauddin (Universitas Terbuka, 2024)
The purpose of this study is to provide an explanation for the actions taken by the local government work unit in Banjar City to stimulate public interest in reading. The work unit of the Regional Public library, situated on Jalan RE. Kosasih in Banjar City, is the subject of the study. Descriptive qualitative research is employed in conjunction with Campbell J.P.'s theory of effectiveness approach to examine the problem of reading interest services at the Banjar City regional public library in detail and depth, thereby facilitating a more comprehensive discussion of its real-world aspects. the data acquisition process was carried out by interviews, field notes and documentation notes. Based on the data that has been reduced and presented, researchers make conclusions that are supported by strong evidence at the data collection stage. The study's findings show that the effectiveness level is very successful. on the program's sustainability up to this point as well as the target's achievement with community involvement in spite of challenges brought on by the budget shortfall. As a served community, educational services are also met on the program satisfaction criteria; nevertheless, in order to improve library flexibility, collaboration with other stakeholders is required. Excellent planning and resource utilization results in a high level of efficiency in the input and output processes that support activities. In the meantime, the overarching objective of this exercise as a teaching tool has been met with the anticipated success.